Evacuation after the Fukushima Daiichi Nuclear Power Plant Accident Is a Cause of Diabetes: Results from the Fukushima Health Management Survey - Hiroaki Satoh; Tetsuya Ohira; Mitsuaki Hosoya; Akira Sakai; Tsuyoshi Watanabe; Akira Ohtsuru; Yukihiko Kawasaki; Hitoshi Suzuki; Atsushi Takahashi; Gen Kobashi; Kotaro Ozasa; Seiji Yasumura; et al. (Journal of Diabetes Research)
The Great East Japan Earthquake and Fukushima Daiichi nuclear disaster in 2011 forced the evacuation of a large number of residents and created changes in the lifestyle of the evacuees. These changes may have affected the evacuees’ glucose metabolism, thereby leading to an increase in the incidence of diabetes. This study included Japanese men and women who were living near the Fukushima Daiichi Nuclear Power Plant in Fukushima prefecture before the disaster. Subjects subsequently underwent annual health checkups with a focus on metabolic syndromes, which were conducted under the Health Care Insurers. Using the Comprehensive Health Check survey, we analyzed changes in the glucose metabolism before and after the disaster. A total of 27,486 subjects underwent follow-up examinations after the disaster, with a mean follow-up period of 1.6 years. After the disaster, the prevalence of diabetes increased significantly, and we observed that the incidence of diabetes was significantly greater among evacuees than among nonevacuees. Furthermore, multivariate logistic regression analysis revealed that evacuation was significantly associated with the incidence of diabetes. In conclusion, this is the first study to demonstrate that evacuation is associated with the incidence of diabetes. This information may be used to guide follow-up recommendations for evacuees.